Rise and fall of vowel length in Slavic - Kortlandt, Frederik (Array, 2018)
My observation that Mate Kapović’s ideas about Slavic accentuation lack a chronological perspective has evoked a furious reaction (Kortlandt 2016b: 478f., Kapović 2017). Since his account can easily leave a false impression on an uninitiated reader, I will here try to clarify the major issues in the simplest way possible. I will limit myself to the five topics that Kapović apparently found most difficult to appreciate: pretonic vowel length, the genitive plural, monosyllabic lengthening, length in medial syllables, and length in Czech monosyllables. The numbers of the stages mentioned below refer to the detailed relative chronology of Slavic phonological developments that I have proposed elsewhere (Kortlandt 1989, 2011: 157-176, 277-309).